2014
DOI: 10.1002/jcla.21731
|View full text |Cite
|
Sign up to set email alerts
|

Serum Level of Macrophage Migration Inhibitory Factor (MIF) in Egyptians With Alopecia Areata and Its Relation to the Clinical Severity of the Disease

Abstract: MIF seems to have an essential role in the etiopathogenesis of AA. So, it is considered to be a promising target in the therapy of autoimmune diseases and as a future predictor of alopecia activity. Anti-MIF therapy might be added as one of the new biological treatments for AA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
8
0
3
Order By: Relevance
“…MIF was originally identified because of its ability to inhibit the random migration of macrophages in vitro. MIF is expressed in hair follicles, and there is a close association between reduced MIF in hair follicles and the development of alopecia areata, which is an autoimmune disease of the skin [ 59 , 60 ]. Interestingly, treatment with TGF-β1 and LiCl induced the expression of MIF in MSCs, and treatment with MIF induced DPC viability for recruitment of the conduction ability.…”
Section: Discussionmentioning
confidence: 99%
“…MIF was originally identified because of its ability to inhibit the random migration of macrophages in vitro. MIF is expressed in hair follicles, and there is a close association between reduced MIF in hair follicles and the development of alopecia areata, which is an autoimmune disease of the skin [ 59 , 60 ]. Interestingly, treatment with TGF-β1 and LiCl induced the expression of MIF in MSCs, and treatment with MIF induced DPC viability for recruitment of the conduction ability.…”
Section: Discussionmentioning
confidence: 99%
“…There is still controversy over attribution of an anti‐inflammatory role to MIF. Although histological studies have shown significant downregulation of MIF in AA lesions, and several studies from other IP sites also agree on its inhibitory functions, recent findings have implicated a proinflammatory role for MIF …”
Section: How Do Immune Privilege Sites Prevent Natural Killer Cell Acmentioning
confidence: 95%
“…Although histological studies have shown significant downregulation of MIF in AA lesions, and several studies from other IP sites also agree on its inhibitory functions, 50-53 recent findings have implicated a proinflammatory role for MIF. 29,[54][55][56][57][58][59][60][61][62][63] Another less emphasized mechanism for preventing NK cells from attacking the MHC-negative cells is the expression of nonclassical MHC-I proteins such as human leucocyte antigen (HLA)-G and HLA-E. These MHCs play a great role in preserving fetomaternal tolerance and ocular IP, but their contribution to HF privilege remains to be elucidated.…”
Section: How Do Immune Privilege Sites Prevent Natural Killer Cell Acmentioning
confidence: 99%
“…So, it is considered to be a promising target in the therapy of autoimmune diseases and as a future predictor of alopecia activity. Anti-MIF therapy might be added as one of the new biological treatments for AA [38].…”
Section: Recent Concepts In the Pathogenesis Of Alopecia Areatamentioning
confidence: 99%